1ISG-011 Assessment of asthma diagnosed population eligible for new monoclonal antibody therapy and related cost in the Veneto region. (24th March 2020) - Degli Esposti, L; Perrone, V; Sangiorgi, D; Menti, AM; Andretta, M
Abstract : Background and importance: Novel treatment approaches for the management of severe refractory asthma include monoclonal antibodies (Mabs). Aim and objectives: The study aimed to estimate the number of the most suitable patients with severe uncontrolled asthma who are eligible for new Mabs therapy and related costs in the Veneto region (Italy). Material and methods: The regional administrative database was retrospectively analysed to identify specific eligibility and assessment criteria. All patients aged ≥6 years with an exemption code for asthma (007) (level 1 patients (L1)) between 1 January 2011 and 31 December 2016 were screened. The following parameters were considered in succession: spirometry (codes: 89.37, 89.38)–(level 2 patients (L2)); inhaled corticosteroids (ICS) in combination with long acting beta adenoreceptor agonists (LABA) and/or theophylline (ATC: R03DA04), and/or antileucotriene (ATC: R03DC), and/or anticholinergics (ATC: R03BB)–(level 3 patients (L3)); high dose ICS therapy (ATC: R03BA, R03AK)–(level 4 patients (L4)); adherence to each medication–(level 5 patients (L5)); asthma hospitalisation (ICD9: 493) or treatment with systemic corticosteroids (ATC: H02)–(level 6 patients (L6)). For each patient level, the mean annual healthcare costs per patient, based on total resource consumption, were assessed. Results: For a total of 4.6 million beneficiaries, aged ≥6 years, 103 138 (2.2%) patients were screened (L1). Spirometry tests were prescribed in 28 611 patients (27.7%) (L2), of whom 13 432 (46.9%) had a prescription for ICS with LABA or other agents (L3). In 5782 (43%) patients treated with previous combinations, high dose ICS therapy was prescribed (L4), and of them, 3307 (57.2%) were treatment adherent (L5) and 1136 (35.2%) had a hospital admission for asthma or treatment with systemic corticosteroids (L6). For this last level of patients, centres specialising in Mabs prescription evaluated eligibility. Total costs of the illness according to disease progression were €1279.6 for L1, €1567.7 for L2, €2045.3 for L3, €2524.2 for L4, €3233.2 for L5 and €4326.2 for L6; overall asthma related treatment and hospitalisation costs were €274.2 for L1, €400.1 for L2, €598.5 for L3, €784.3 for L4, €1118.4 for L5 and €1449.9 for L5. Conclusion and relevance: This analysis allowed estimation of the number of asthma patients eligible for Mabs therapy in the Veneto region. Our findings on healthcare costs highlighted that the average cost per patient increased by severity level. Post marketing, it will be possible to assess the appropriateness of Mabs prescriptions through indicators such as over- and under-use. References and/or acknowledgements: No conflict of interest.